Comparative Study on Post Mortem Analysis of Sodium and Potassium Levels of Vitreous Humour and Synovial Fluid in Determining Time Since Death - Gurpreet Singh; DK Sharma; Deepali Pathak; Sumanta Dutta (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Time since death (TSD) is the period between the death and time of examination of a body. Numerousstudies conducted on analysis of potassium in vitreous humour have shown that the vitreous potassium levelsincrease with rise in TSD. Studies done on postmortem biochemistry of synovial fluid have proposed a positivelinear relationship between potassium and TSD. But, very few authors have compared findings of these two fluids.So, this study was undertaken to compare the accuracy of determining post-mortem interval from Sodium andPotassium levels of vitreous humour and synovial fluid.Methods: A total of 140 cases were taken with certified time of death. These were divided into 7 groups i.e.0-6 hours, 6-12 hours, 12-18 hours, 18-24 hours, 24-30 hours, 30-36 hours and above 36 hours. Vitreous humour andSynovial fluid from knee joint were aspirated from both sides of body and were analyzed using Medica EasylyteNa/K Analyser. Results were obtained using SPSS 24 software.Conclusions: Potassium has a strong positive correlation with TSD in both fluids. Sodium has weak negativecorrelation. There is no difference between values of both sides. There is no statistically significant differencebetween values of Vitreous humour and Synovial Fluid. Hence, both can be used alternatively.